Minimum Quality Standards and Collusion - Giulio Ecchia; Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1995)
We model the introduction of a minimum quality standard in a vertically differentiated duopoly. We extend the literature in determining the standard endogenously, showing that the maximisation of social welfare entails an increase in the surplus accruing to consumers served by the low quality firm and a decrease in the surplus of the remaining consumers. Then, we consider the effects of the standard on the stability of price collusion, proving that the standard makes it more difficult for firms to collude if consumers are sufficiently rich.
Keywords: 330